2019
DOI: 10.14202/vetworld.2019.1657-1667
|View full text |Cite
|
Sign up to set email alerts
|

Protein metabolic changes and nucleolus organizer regions activity in the lymphocytes of neonatal calves during the development of respiratory diseases

Abstract: Background and Aim:Calfhood disease is an important problem in dairy farming that could cause significant effects on heifer survival and productivity and has economic and welfare effects. Total protein concentration in the blood serum could be one of the predictors of bovine respiratory disease (BRD) in newborn calves. The number of active nucleolus organizers could be used to assess the viability of the protein synthesis system in cells and tissues. We aimed for a comparative assessment of the dynamics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…Immune cells metabolism have been shown to differ during GVHD pathophysiology and associate significantly (Kalaeva et al, 2019). Various metabolic phenotypes have been identified in inflammatory disorders (Kominsky et al, 2010;Kang et al, 2015).…”
Section: T Cells Metabolism and Allo-hsctmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune cells metabolism have been shown to differ during GVHD pathophysiology and associate significantly (Kalaeva et al, 2019). Various metabolic phenotypes have been identified in inflammatory disorders (Kominsky et al, 2010;Kang et al, 2015).…”
Section: T Cells Metabolism and Allo-hsctmentioning
confidence: 99%
“…The effector T cells and an inflammatory cytokine storm together affect the host tissue causing further damage and perpetuating the cycle that aggravates GVHD, considering phase III. Figure modified from (Ferrara et al, 2009) Lancet 2009373: 1,550-61. have significant association with GVHD pathology (Kalaeva et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…The milk acidity and density were within the regulatory limits set by the interstate standard for raw milk. Seasonal differences in milk composition and properties were previously studied by Kalaeva et al [26] and Kakimov et al [27]. The authors found a slight increase in milk acidity in the autumn-winter period, which can be explained by changes in animal nutrition.…”
Section: Discussionmentioning
confidence: 83%
“…Numerous studies have found that the use of probiotics as growth stimulators and therapeutic and prophylactic agents for young farm animals is very encouraging, and the application scope in practical animal husbandry is unlimited [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%